Global investment flows transformation during the COVID-19 pandemic (Economics and region, 2021)
The impact of the coronavirus pandemic on investment decisions in international economic activity has been analyzed and the concepts of capital flight and net capital inflows have been considered. Sources of investment have been systematized, from which companies have the opportunity to obtain resources to improve their work. Among the main sources of investment foreign aid in the form of grants, loans, etc. has been considered as a rather controversial category, as there were cases when state foreign aid had a positive impact on the economy of the recipient country and along with them there are many examples of failure to use such aid. Currently, there is an intensification of the global investment movement, as the number of countries that have increased financial resources and, as a result, have a surplus, is increasing every year. A well-established investment movement has significant positive effects not only for an enterprise that receives them, but also for a state as a whole. International organizations regulate relations between member countries, determine certain rules of individual states’ or even regions’ economic development, impose restrictions or, conversely, promote the intensification of activities in certain areas to certain countries (enterprises that represent them). Coronavirus has negatively affected global investment flows, leading to a decline in key economic indicators in all countries. During the crisis caused by the pandemic, the rules of the game in the investment field have changed significantly – there have been other priority areas of investment and the criteria by which investors choose objects for financing.
Keywords: foreign direct investment; investment market; globalization; COVID-19; world economy